PdSn nanocatalysts supported on carbon nanotubes synthesized in deep eutectic solvents with high activity for formic acid electrooxidation. Issue 65 (23rd June 2016) - Wang, Rui-Xiang; Fan, You-Jun; Liang, Zhi-Rong; Zhang, Jun-Ming; Zhou, Zhi-You; Sun, Shi-Gang
Abstract : A novel strategy in DESs for the fabrication of MWCNTs-supported PdSn alloy nanostructures is reported. The prepared PdSn/MWCNT shows remarkably improved electrocatalytic performance towards formic acid oxidation reaction. Abstract : Deep eutectic solvents (DESs) are being increasingly used in electrochemically controllable synthesis of functional nanomaterials because of their unique merits ( e.g., high conductivity, wide electrochemical windows and environmental friendship). Herein, we report a novel strategy in DESs for the fabrication of multi-walled carbon nanotubes (MWCNTs)-supported Pd-based alloy nanostructures. Using a NaBH4 solvothermal reduction process in DESs, highly active PdSn alloy nanocatalysts supported on MWCNTs towards the formic acid oxidation (FAO) reaction were synthesized for the first time. The as-synthesized materials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray (EDX) spectroscopy, X-ray photoelectron spectroscopy (XPS) and electrochemical tests. The results demonstrate that the PdSn nanocluster structure with a rough surface provides a high density of catalytically active sites and thereby increases the electrochemically active surface area. There is a strong charge transfer interaction between Pd and Sn in the PdSn/MWCNT catalyst due to its high degree of alloying. The electrochemical studies indicate that the PdSn/MWCNT shows remarkably improved electrocatalytic performance towards FAO compared to Pd/MWCNT and commercial Pd/C catalysts. This study suggests an effective synthesis strategy for Pd-based electrocatalysts with high performance for DFAFCs applications.